The Reflection of Wabi Sabi in the Novel Joseito by Dazai Osamu - Rima Devi; Aminah Hasibuan; Ferdinal Ferdinal (Bina Nusantara University, 2021)
The research examined the life’s perspective of the author that was reflected in wabi sabi in the novel ‘Joseito’ by Dazai Osamu. The life of the Joseito character described by Dazai Osamu in the Joseito novel had individual values (honne), and Joseito desired to equate it with collective values (tatemae). However, Joseito could not unite the two contradictory values and accepted the contradiction. The method used was descriptive qualitative, with the sociology of literature approach and focused on the sociology of the author using the concept of wabi sabi. Data on wabi sabi were collected from reading Joseito’s novels. The research results find that Dazai Osamu sincerely accepts the contradictions in Japanese society because Dazai can place himself where he is. Dazai is willing to accept contradictions in Japanese society by understanding the meaning of wabi sabi. He learns to appreciate, accept what it is, and be grateful for the contradictions in society because these contradictions can establish harmony in a beautifully ordered life through wabi sabi.